TRANSFORMASI PARIWISATA TUBAN MELALUI APLIKASI 'TUBAN TOURISM': MENGOPTIMALKAN POTENSI WISATA BERBASIS ANDROID - Zahara Aliya, Izra Noor; Ridwandono, Doddy (JUSTIFY : Jurnal Sistem Informasi Ibrahimy, 2024)
Technological advances, especially in Android-based applications, are key in the transformation of the world of tourism, especially in Tuban, East Java. Tuban, which is rich in natural, historical and cultural destinations, does not yet have a digital platform that provides complete tourist information. Therefore, an Android-based application called "Tuban Tourism" was developed to increase promotion and access to tourism information in Tuban, East Java. The research methods used include observation, literature study, needs analysis, design and coding as well as implementation using Android Studio and the Kotlin programming language. By utilizing technological advances, this application is expected to make it easier for tourists to plan trips, providing complete information about tourist destinations, interactive maps, event schedules, recommendations for places to eat and accommodation. Through the use of the features provided by this application, it is hoped that it can increase the attractiveness of Tuban tourism and contribute to the local economy